Analisis Nilai Sosial pada Album Lirik Lagu Liza Aulia - Harahap, Ririn Dayanti; Rizeki, Wahyuni; Suriyanti, Yuni; Zuhra, Zuhra; Fathonah, Sephia Fathonah; Rizqina, Azkiya; Istiqomah, Istiqomah (Medan Resource Center, 2024)
Music holds a central place in human life, not merely as entertainment but as a reflection of cultural identity and social behavior. This study explores the social values embedded in the lyrics of Liza Aulia’s songs, which remain understudied in academic discourse. The research seeks to answer how Liza Aulia's song lyrics convey various social values, including religious, moral, social-cultural, economic, political, educational, aesthetic, and humanistic elements. Employing a qualitative descriptive method with a literature study approach, this research analyzes the lyrical content of eight of her albums: Keuneba Endatu, Kutidieng, Mala Bayeun, Hate Keu Allah, Jamboe Nyo, Seulayang, Adat, and Likok Pulo. The findings reveal that Liza Aulia’s lyrics are rich with multidimensional values that reflect the sociocultural context of Acehnese society. This study contributes a novel perspective to the academic understanding of regional music by framing it within a structured cultural analysis, thereby emphasizing the relevance of local musical expressions as carriers of social meaning.